Flower and Pod Source Influence on Pea Weevil (Bruchus pisorum) Oviposition Capacity and Preference - Aznar-Fernández, Thaïs; Rubiales, Diego (Frontiers in Plant Science, 2019)
Bruchus pisorum is an insect pest causing major damage to pea seeds worldwide. Control is difficult and limited resistance is available. In this work we studied the effects of pollen and pod source on insect fecundity and oviposition by comparing resistant and susceptible Pisum spp. accessions and non-host (Lathyrus sativus and Vicia faba) species. A first no-choice assay revealed that the source of flower offered to adults for feeding might retard oviposition (the case of V. faba), reduce fertility (P. sativum ssp. syriacum, P. fulvum and V. faba) or increase adult mortality (V. faba and P. sativum ssp. syriacum). A second no-choice assay with all adults fed with pollen of the same pea cultivar showed significant effect of the source of pods offered. Oviposition was reduced on pods of some resistant Pisum accessions, but particularly low on pods of the non-hosts, being retarded if ever happening and coupled with high mortality of adults. This was confirmed in a third experiment consisting on dual-choice assays showing reduced egg laying in V. faba, L. sativus, P. fulvum and P. sativum ssp. syriacum compared to the commercial variety pea used as a control (Messire).